DEVELOPMENT OF QUIZIZZ LEARNING MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES IN SOCIAL STUDIES LEARNING AT SMP NEGERI 2 TERNATE CITY - Muhammad Ali Wahid; Rusman Rasyid; Ramdani Salam (SOSIOEDUKASI, 2026)
This research aims to develop Quizizz-based learning media and determine its feasibility and effectiveness in improving student learning outcomes in Social Sciences (IPS) subjects at SMP Negeri 2 Ternate City. The background of this research is based on the low learning outcomes of students caused by the use of learning media that is less varied and not optimal in utilizing digital technology. The research method used is research and development with stages including needs analysis, media design, product development, trial, and evaluation. The subject of the study is a student of the State Junior High School 2 Ternate City. Data collection techniques are carried out through observation, questionnaires, and learning outcome tests. The results of the study show that the Quizizz learning media is declared feasible to use based on the results of expert validation and positive student responses. In addition, the use of Quizizz media has been shown to be effective in improving student learning outcomes, which is shown by the increase in average scores and the percentage of learning completeness after the application of the media. Thus, Quizizz learning media can be used as an alternative to innovative and effective social studies learning media at SMP Negeri 2 Ternate City.